Developing graphical visualization for understanding the pattern of movie streaming on iflix in Malaysia / Noorsyahirah Nasri - Nasri, Noorsyahirah (2022)
Thanks to recent improvements in digital technology, movie streaming has become more adaptable and accessible to a wider variety of people. Having an accurate and timely projection of box-office demand is crucial when it comes to planning and making decisions in this industry. Because the data is provided in dataset format, it is likely to include a large amount of information, making it difficult for certain individuals to interpret and comprehend the material based on their own viewpoint. Data visualization is required to gain a better understanding of the facts surrounding the movie streaming pattern. As a result, this project was planned to create a graphical visualization dashboard using Microsoft Power BI for analyzing movie streaming patterns, which was divided into four phases: planning, analysis, development, and implementation. This initiative enables related parties to better understand the movie streaming patterns on iflix, particularly in Malaysia and make better future decisions about release dates, marketing strategies, and costs can be made. This project used Python as a programming language and Anaconda as a platform to analyses the pattern of movie streaming on iflix in Malaysia and display the data using a Microsoft Power BI dashboard. The significance of this undertaking will have a beneficial effect on society as a whole. Having visual presentations make statistical data analysis on the movie streaming pattern more readily accessible and participatory for the general audience, this project may help individuals better comprehend statistical data analysis on the movie streaming pattern. The findings of this project allow decision maker to see the pattern of movie streaming on iflix in Malaysia using a Microsoft Power BI dashboard.